Luffa/Epoxy Composites: Electrical Properties for PCB Application - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2020)
Traditional printed circuit board (PCB) laminates such as FR4 types are formed using epoxy resin and glass fiber. The most important problem with waste PCB laminates is that their recycling cycle is too long. Herein, we aimed to show whether it is possible to use plant-based fibers instead of petroleum-based fibers. In this study, we have fabricated alternative eco-friendly Luffa fiber-reinforced/epoxy PCB (Luffa-PCB) laminates using Luffa fiber instead of glass fiber. We examined the properties of Luffa-PCB laminates for potential applications as PCBs in terms of frequency dependence of dielectric permittivity, capacitance, ac conductivity, impedance, and electric modulus by using impedance spectroscopy method in a frequency ranging from 10 Hz to 10 MHz. Furthermore, we investigated the electrical resistivity properties of Luffa-PCB laminates using electrometer/high resistance meter and resistivity test fixture. All the results were compared with commonly used FR2- and FR4-type PCB laminates. According to the results obtained, it has been found that the produced Luffa-PCB laminates have adequate properties as an alternative to traditional laminates. Thus, a very important step is taken to solve the recycling problem by using plant-based fibers instead of glass fibers.
Keywords: Laminates; Optical fiber communication; Conductivity; Resistance; Glass; Recycling; Fixtures; Bio-based printed circuit boards (PCBs); biocomposite; electrical properties; natural fiber; recycling; PRINTED-CIRCUIT BOARDS; MECHANICAL-PROPERTIES; MODULUS; DESIGN; CONDUCTIVITY; GLASS